Direct Oral Anticoagulants in Asian Patients with Atrial Fibrillation: Consensus Recommendations by the Asian Pacific Society of Cardiology on Strategies for Thrombotic and Bleeding Risk Management. Issue 1 (2021) - Chong, Daniel TT; Lee, Lai Heng; Li, Yi-Heng; Quek, David KL; Andreotti, Felicita; Jiang, Jun; Johar, Sofian; Verhamme, Peter; Hasegawa, Koji; Seow, Swee-Chong; Dalal, Jamshed J
No abstract available